Servitudes and Options in The Indonesian Translation of Terman’s By Balloon to The Sahara - Yusuf Arimatea Neno; Harris Hermansyah Setiajid (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
In the realm of translation, balancing the preservation of meaning and style while adapting to the linguistic and cultural context of the target language is crucial. This study investigates the application of Vinay and Darbelnet's concepts of servitude and option, referred to as "procedures," in the Indonesian translation of Terman's children's book, By Balloon to the Sahara. This study examines instances of servitude, illustrating the obligatory changes the translator made due to inherent differences between the source and target languages. These changes, driven by grammatical correctness and naturalness, are necessary to create a coherent and accessible translation for Indonesian readers. The research also explores instances of option, showcasing the translator's non-obligatory choices, which reflect their personal style, preferences, or a shift in emphasis. The findings of this study highlight the importance of understanding and applying the concepts of servitude and option as translation procedures, particularly in children's literature, where comprehension and readability are of paramount importance. By employing these procedures, translators can produce engaging and accessible translations that preserve the original text's meaning and style while catering to the linguistic and cultural context of the target audience. This study contributes to the field of translation studies by demonstrating the effectiveness of servitude and option in the translation of children's literature, paving the way for future research in this area.